Síntese de novos adsorventes a partir de resíduos de pó de rocha vulcânica oriundos de mineradoras do Rio Grande do Sul/Brasil - Rossatto, Diovani Leindcker (2024)
The demand for new materials for the treatment of effluents contaminated with waste has high scientific and economic/industrial relevance. Thus, this work sought to verify the potential of volcanic rock powder residues from the extraction of semi-precious rocks in the state of Rio Grande do Sul, Brazil, as precursors in the production of new adsorbents for removing dyes and metallic ions from water, and thus, adding value and give an appropriate destination to this waste. Waste volcanic rock powder from Ametista do Sul (AME) and Nova Prata (NP) were the starting materials. These were used “in natura” or subjected to the process of alkaline activation at 60 °C and alkaline fusion at 550 °C. Analysis of the initial samples by X-ray fluorescence (XRF) revealed that they are mainly composed of aluminum, calcium, iron and silicon oxides, which corroborates the presence of numerous crystalline phases observed in the X-ray diffraction (XRD) spectra. Furthermore, by XRD analysis of the synthesized samples, alkaline fusion proved to be more efficient that alkaline activation in dissolving crystalline phases and consequently in the formation of the amorphous phase. Moreover, adsorption tests with acid green 16 (AG16) and acid red 97 (AR97) dyes and Ag+ , Co2+ and Cu2+ ions indicated the feasibility of using residual volcanic rock powder as raw material for the production of adsorbents alkaline activated with sodium hydroxide, with the samples synthesized by alkaline fusion showed better results in removal and adsorption capacity for all contaminants used in the study. Applying the rotational central composite design 22 (CCRD) it can be seen that the independent variables alkalinizing ratio NaOH(s.)/volcanic rock (VR) and temperature considerably influence the characteristics and synthesis of adsorbent materials by alkaline fusion, which in turn reflects in the results achieved in the adsorption of contaminants. Furthermore, it was determined that the temperature of 550 °C , the NaOH(s.)/RV mass ratio equal to 1 and the precursor sample of Nova Prata (NP) was the most satisfactory synthesis route to obtain high values of adsorption capacity (q, mg g-1 ) and removal (R, %) for the studied contaminants, as well as the optimization of the physical characteristics of the material. The adsorption kinetic data fit the pseudo-second order mathematical model with fast adsorption and the process equilibrium was reached after 30 min for dyes and 40 min for metal ions. The Sips model proved to be adequate to represent the adsorption isotherms of metal ions and the AR97 dye, while the BET model represented the isotherms of the dye AG16. Additionally, the adsorption of Cu2+(aq.) ion, AG16 and AR97 dyes was endothermic, while the adsorption of Ag+ (aq.) was exothermic. Finally, even after numerous subsequent adsorption cycles, the NP.F sample maintained high reusability, suggesting that the sample is qualified to be an adsorbent for removing contaminants from liquid effluents. In conclusion, NP can be easily converted into an efficient inorganic adsorbent for dyes and metals.